(untitled) (Experimental biology, 2009)
In our research we have been investigated histological experiment on the tissue of rat’s liver, which were exposed to chronic effect of hexane (1/20 ЛК5о equal to 627000 mg/m³). As a result we found that high content of hexane represented the reduction of glycogen content, accumulation of fat tissue and lead to the destruction of liver’s function. Therefore in our experiment we determined the adverse effect of hexane on the liver’s tissue.